La traduction numérique ou automatique, quelle place occupe- t-elle dans notre vie aujourd’hui ? - مرعي ليليان (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Digital translation has become an essential part of our daily lives. Internet websites are competing to produce and develop digital translation software and offer them for free. This software is used by different sectors in different specialties. The user can get a translation of his/her text by a simple click. This is in line with the main principle of modern technology, that is, speed and flexibility. However, the use of digital translation software couldn’t escape criticism especially from linguists who continuously attract attention to the dangers, linguistically speaking, of totally depending on this software in translating texts, since an essential part of the meaning these texts aim to convey is lost in the process. Hence, to what extent can we, as users of this software, understand the concerns of those linguists? And under what conditions can we endorse digital translation?